Phenytoin‐induced choreoathetosis after serial seizures due to traumatic brain injury and chronic alcoholism. Issue 12 (17th October 2018) - Finsterer, Josef; Keller, Hans; Reining‐Festa, Alice; Enzelsberger, Barbara; Weidinger, Franz
Key Clinical Message: Intravenous phenytoin (PHT) for suspected seizures may trigger severe choreoathetosis. Discontinuation of PHT results in immediate and complete resolution of hyperkinesias. Co‐medication with valproic acid, levetiracetam, tranquilisers, and anesthetics or alcohol presumably do not modify this adverse effect of PHT. Choreoathetosis can be easily misinterpreted as seizures. Abstract : Intravenous phenytoin (PHT) for suspected seizures may trigger severe choreoathetosis. Discontinuation of PHT results in immediate and complete resolution of hyperkinesias. Co‐medication with valproic acid, levetiracetam, tranquilisers, and anesthetics or alcohol presumably do not modify this adverse effect of PHT. Choreoathetosis can be easily misinterpreted as seizures.